Surround suppression maps in the cat primary visual cortex - Vanni, Matthieu P.; Casanova, Christian (Frontiers in Neural Circuits, 2013)
In the primary visual cortex and higher-order areas, it is well known that the stimulation of areas surrounding the classical receptive field of a neuron can inhibit its responses. In the primate area MT, this surround suppression was shown to be spatially organized into high and low suppression modules. However, such an organization hasn’t been demonstrated yet in the primary visual cortex. Here, we used optical imaging of intrinsic signals to spatially evaluate surround suppression in the cat visual cortex. The magnitude of the response was measured in areas 17 and 18 for stimuli with different diameters, presented at different eccentricities. Delimited regions of the cortex were revealed by circumscribed stimulations of the visual field (“cortical response field”). Increasing the stimulus diameter increased the spread of cortical activation. In the cortical response field, the optimal stimulation diameter and the level of suppression were evaluated. Most pixels (3/4) exhibited surround suppression profiles. The optimal diameter, corresponding to a population of receptive fields, was smaller in area 17 (22 deg.) than in area 18 (36 deg.) in accordance with electrophysiological data. No difference in the suppression strength was observed between both areas (A17: 25%, A18: 21%). Further analysis of our data revealed the presence of surround modulation maps, organized in low and high suppression domains. We also developed a statistical method to confirm the existence of this cortical map and its neuronal origin. The organization for center/surround suppression observed here at the level of the primary visual cortex is similar to those found in higher order areas in primates (e.g. area MT) and could represent a strategy to optimize figure ground discrimination.